Implementation of the SIMDA FMIS Application in the Local Government of Samarinda - Chairunnisa, Farach; Jamaluddin (Applied Business and Administration Journal, 2026)
This study aims to determine the effect of implementing the SIMDA FMIS application on the quality of local government financial statements, moderated by human resource competence. This objective is based on the fact that, currently, the preparation of government financial statements is supported by an application, namely SIMDA FMIS. This application must be operated by competent personnel to produce high-quality financial statements that support informed decision-making. The method used is quantitative, and the data collection technique involves a questionnaire distributed to 43 employees in accounting/finance departments. This study used Smart-PLS version 4.1 as the analysis tool. The results showed that implementing the SIMDA FMIS application had a significant and positive effect on the quality of local government financial statements. However, human resource competency did not moderate this relationship.